THE POLITENESS STRATEGIES: MALE AND FEMALE POLITENESS STRATEGIES IN A GROUP DISCUSSION - Ali, Helena Verusha (English Community Journal, 2023)
Politeness is a strategy used to have interaction in daily conversation.  This study investigates the following questions: (1) What types of FTAs (Face Threatening Acts) and politeness strategies frequently used by females and males in a short interview’s conversation?, and (2) Is there any effect of the relation of close friendship toward politeness?. The method used was qualitative research. The five participants are included in terms of 2 females and 3 males in the age of around 30 - 40 from different various ethnic groups, occupations, and status. The instrument used was a FGD (Focus Group Discussion)  to collect the data from the participants’ utterances as a source of data with the controversial topic. The procedures used to analyze the data were listening to the recorded  utterances, transcribing the raw data and translating them into English, classifying the raw data of utterances into female and male section to find out the differences of their politeness and identifying the FTAs and analyzing the types of politeness strategies used.  Based on the findings, female participants’ dominance types of FTA are criticized, followed by complaining, which indicates an impolite degree. On the other hand, male participants’ dominance types of FTAs used are confessing, which means a polite degree. Second, the close relation of friendship influences the degree of politeness, which produces the opposite result from the previous studies. In these findings, the data showed that females are less polite than males. Based on these factors, women may react less politely in the data, but according to the three elements, it must be taken into consideration that the impact is reasonable.